2015
DOI: 10.1111/jfpp.12670
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Hydrolytic Capacities of Aspergillus oryzae Proteases on Soybean Protein Using Artificial Neural Networks

Abstract: An artificial neural network (ANN) model was established to predict the hydrolytic capacities of Aspergillus oryzae proteases on soybean protein. The available training data were split in two subsets: training and testing data, which comprised 25 and six groups of proteases, respectively. These data served as the inputs of ANN to predict small peptide content, degree of hydrolysis and free amino nitrogen content. This network included three neurons in the single hidden layer with a low mean squared error. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A back‐propagation algorithm (BP) was used to implement the supervised networks. This study used one hidden layer feed‐forward network structure with input and output layer, since one hidden layer has been found to be adequate in most cases (Li et al, ; Martinez et al, ). In order to better predict the percentage change of IMP, the number of neurons in the hidden layer was assigned through trial and error, as shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…A back‐propagation algorithm (BP) was used to implement the supervised networks. This study used one hidden layer feed‐forward network structure with input and output layer, since one hidden layer has been found to be adequate in most cases (Li et al, ; Martinez et al, ). In order to better predict the percentage change of IMP, the number of neurons in the hidden layer was assigned through trial and error, as shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Only a single layer was used in this implementation because more layers may cause the local minimum problem (Rai et al, 2005;Li et al, 2016;Martinez et al, 2012). The optimal topology was chosen by determining the minimum error during testing.…”
Section: Analysis Of the Artificial Neural Network Modelmentioning
confidence: 99%
“…As for the protein hydrolysis, Abakarov et al (2011) satisfactorily modelled the kinetics of enzymatic hydrolysis of squid protein with subtilisin using the reaction time and the substrate concentration as input variables. Buciński et al (2008) and Li et al (2016) evaluated the variation of DH during the hydrolysis of bovine haemoglobin and pea proteins, respectively. Li et al (2006) developed a predictive model for the production of antioxidant peptides from fish proteins taking into account a number of input variables such as pH, temperature, hydrolysis time, muscle/water ratio and enzyme/substrate ratio.…”
mentioning
confidence: 99%